TRIP GENERATION AND MODE CHOICE ANALYSIS OF FREIGHT INTER CITY TRANSPORTATION - PUTRA (NIM 25098065), MISDAR
Transportation problem including freight one needs to be planned and well managed. These are specially in big cities, even in Indonesia there are many cities have more than two billions populations. This research concerns on trip generation and mode choice on freight transportation problem in inter urban, in this case from Bandung to Jakarta. This research objective is identifying of characteristic, important variable and modeling of trip generation and mode choice of entire freight transport. Analysis of trip generation modeling based on freight volume data as dependent variable and socio-economic in study area as independent variable. Applied unit is annual serial zone system analysis data while calibration model used Multiple Linear Regression. Analysis of mode choice modeling based on questionnaire distributed to selected companies, especially textile companies with using Stated Preference surveys. Major problems occuring on this research is low returning rate on feed backing data, it was about 15 % with long time consuming, almost a year. Furthermore, model -calibration used both Multiple Linear Regression and Maximum Likelihood analysis approaches.